KINERJA RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN JASA DI BURSA EFEK INDONESIA PERIODE 2009-2014 - Ayu Widuri Sucipto; Muazaroh Muazaroh (Journal of Business & Banking, 2016)
Identifying financial distress condition is important because it can be an early warning system before bankcruptcy. This condition can be predicted using models that have developed by many researchers. The purpose of this research is to describe and analyze the effect of the return on assets, current ratio, debt to equity ratio and total asset turnover towards condition of financial distress in service sector listed in Indonesian Stock Exchange (IDX) in the year 2009-2014. The data analysis technique is logistic regression. The sample consist of 60 data observed of the firms with positive earning before tax for the two consecutive years and 60 data observed of the firms with negative earning before tax for the two consecutive years. The result of this research shows thatreturn on asset significantly affects to condition of company financial distress. Whereas debt to equity ratio, current ratio and total asset turnover do not significantly influenceto condition of company financial distress.So, companies should pay attention to productivity in the future to maintain the effectiveness of the management.